Bus seat suspension modification for pregnant women - Gohari, Mohammad (IEEE, 2012)

(untitled)
The physical safety and mentally health of pregnant females are very important. Uterine blood flow can increase in low frequencies and it is harmful for pregnant mothers. Long term trips sometimes are not avoidable and pregnant persons have to do that. In this study, special bus seat suspension was design and optimized based on pregnant biodynamic model. Artificial neural network method was used for optimization of seat to womb vibration transmissibility. Finally, after optimizing this suspension is able to attenuate unwanted vibration of womb near 85%. Therefore, it is required to fabricate and use this suspension in buses for out of city journeys.